Evaluation of Body Weight, Serum Glucose Level and Oxidative Stress Parameters of Streptozotocin-Induced Diabetic Rats Administered Insulin and Alkaloid Leaf Extract of Jatropha tanjorensis - Umoh, Idongesit Bassey; Ukoh, Imoh Emmanuel (Darul Yasin Al Sys, 2026)
Diabetes mellitus (DM) is known to reduce body weight and induce oxidative stress. Hence, this study evaluates the effects of alkaloid leaf extract of Jatropha tanjorensis (ALEJT) on body weight, serum glucose, and oxidative stress parameters in streptozotocin (STZ)-induced DM rats to delineate its possibility as a better therapeutic agent compared to insulin in the treatment of DM. Forty female albino rats (150–200 g) were grouped into four (n = 6). Group 1 served as normal control. Diabetes was induced in Groups 2, 3, and 4 rats by intraperitoneal (i.p.) administration of a single dose of STZ (80 mg/kg) dissolved in citrate buffer (pH 4.5) to overnight-fasted rats. After 72 hours of injection, rats with fasting blood glucose ≥ 200 mg/dL were deemed diabetic. Group 2 served as diabetic control; Group 3 diabetic rats were treated with ALEJT (500 mg/kg orally), while Group 4 was treated with insulin (2 IU/kg/day, i.p.) for 21 days. Changes in body weight and serum glucose levels were assayed within 21 days, after which the rats were sedated with 60 mg/kg of ketamine-hydrochloride, and blood samples were collected via cardiac puncture; serum was used for antioxidant (glutathione [GSH], superoxide dismutase [SOD], glutathione peroxidase [GPx], catalase [CAT], total antioxidant capacity [TAC], and malondialdehyde [MDA]) assays using standard methods. There was no variation in the weight of diabetic rats treated with ALEJT. Percentage growth rate was significantly reduced in the untreated and treated diabetic rats. Glucose levels increased (p < 0.001) in diabetic rats compared with the control. Diabetic control showed a significant decrease in GSH, SOD, TAC, and GPx, while MDA levels increased (p < 0.001) compared with the control. The levels of SOD, GPx, and TAC increased, while MDA decreased significantly (p < 0.001) in the treated groups compared with the diabetic control. GSH increased in insulin (p < 0.01) and ALEJT (p < 0.001) treated rats compared with the diabetic control. GSH and GPx increased significantly in ALEJT-treated rats (p < 0.001) compared with insulin-treated rats. ALEJT was more effective in protecting against weight loss and reversed the levels of GPx and GSH better than insulin. ALEJT could serve as a potential natural and safe remedy for the management of DM.